ANALISIS REMBESAN PADA BENDUNGAN CENGKLIK MENGGUNAKAN METODE RESISTIVITAS KONFIGURASI SCHLUMBERGER DAN UJI PERMEABILITAS UNTUK MENGHITUNG DEBIT REMBESAN - Fajar Waskito; Tony Yulianto; Dwiyanto Joko Suprapto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Resistivity method is one of the geophysical method that used to determine the subsurface structure from the resistivity value. The research uses resistivity method with Schlumberger configuration. The measurement have been done in Cengklik Dam which is located in the Ngargorejo village, Ngemplak districts, Boyolali, Central Java. Cengklik dam is used for irrigation, fish farms and tourism. The conditions of Cengklik dam is awful. There are a lot of cracks on the dam body and a spring appears in the southwest of the dam. So, we assumed that there are seepages on the dam. We get the potential and current value from aquisition and they used to calculate the apparent resistivity. IP2WIN software use to calculate and modeling to get the true resistivity and depth of each layers. Then they used as an input on Progress software to get the 3 dimensional modeling using Rockwork 15 software. The model interpreted with geological information to know the lithology. There is a seepage area on the tuff layer and the discharge seepage obtained by using the Slide 6.0 software. The discharge amount of seepage as 9,4576x10-5m3/s.